Point-of-care ultrasound in early diagnosis and monitoring of deep abscess in newborns: a case report of two cases - Bang Du; Bang Du; Fengdan Xu; Fengdan Xu; Biying Deng; Biying Deng; Baimao Zhong; Baimao Zhong; Ning Li; Ning Li; Xiaoguang He; Xiaoguang He (Frontiers Media S.A., 2024)
ObjectiveThis study sought to analyze the value of point of care ultrasound (POCUS) in early diagnosis and monitoring of deep abscess in newborns.MethodsRetrospective analysis of the clinical data of two newborns admitted to the Neonatal Intensive Care Unit (NICU) of our hospital and diagnosed with deep abscess of the newborn. Combined with literature analysis, the value of POCUS in early diagnosis and monitoring of deep abscess of the newborn was evaluated.ResultsThe two newborns reported in this article were all admitted to NICU due to" "fever". POCUS was used to assist in early diagnosis of "liver abscess" and "lung abscess". Subsequently, POCUS was used to monitor lesion changes and adjust treatment plans. All patients were cured and discharged with a good prognosis.ConclusionsDeep abscesses in newborns are very rare and often life-threatening, but apart from fever, they often have no specific clinical manifestations and are easily misdiagnosed or missed. POCUS, as a bedside auxiliary examination tool, has high accuracy, radiation free, non-invasive, and convenient, and has high diagnostic and monitoring value in early diagnosis and monitoring of deep abscess in newborns.